Detection of Methicillin-resistant Coagulase-positive Staphylococci (MRCPS) Isolated from Dogs Hospitalized to Kasetsart Veterinary Teaching Hospital by Duplex PCR - Sampao, Ronnapat; Lawhavinit, Ongard (Journal of Mahanakorn Veterinary Medicine, 2018)
At present Methicillin-resistant coagulase-positive Staphylococci (MRCPS) in dogs became a serious problem. For the principle diagnosis disk diffusion is most often used for drugs susceptibility by disk diffusion but there were some limited conditions, number of bacteria, time for incubated, temperature, and pH. In this study we used duplex PCR technique which confirmed the result from disk diffusion with mec A gene and fem B detection. 115 samples were collected from nasal swab and wound swab from dogs hospitalized to veterinary hospital. 110 samples were coagulase-positive Staphylococci (nasal swab = 60, wound swab = 50. There were 16 samples positive for methicillin-resistance, 2 were intermediated by disk diffusion but 17 were positive including one of intermediated group and 1 was negative from detection with Duplex PCR. This study shown that there were difference results among 2 techniques which may be some disadvantage of disk diffusion on the other hand Duplex PCR is gold standard for detection methicillin-resistant coagulase-positive Staphylococci (MRCPS). So detection for methicillin-resistant coagulase-positive Staphylococci (MRCPS) has to use Duplex PCR.